The Future of Education: Kastem-Enabled Interactive E-Books Unveiled - Riyanto, Riyanto; Yanti, Fitri April; Suryadi, Didik (International Journal of Asian Education, 2023)
This research aims to design an interactive e-book containing Kastem and its development guide. Kastem acronyms for character, science, technology, engineering, and mathematics. The research design used is ADDIE at the analysis and design stages. The population consisted of all elementary school students in Bengkulu City in grades 1, 2, and 3. The research sample was conducted by purposive random sampling of as many as 820 students. Data collection using questionnaires, interviews, and tests. Data analysis was done descriptively. The results of the design of the interactive booklet containing Kastem and its guide have the characteristics of an interesting, familiar, concrete, specific theme. They are equipped with guiding questions or trigger questions at the beginning of the sub-chapter, as well as combining elements of student character and six media types.